A Prey-Predator Dynamics with Square Root Functional Responses and Strong Allee Effect - Pal, D.; Biswas, S.; Mahapatra, G. S.; Samanta, G. P. (Journal of Applied Nonlinear Dynamics, 2026)
The major aim of this paper is to study the dynamical behaviour of a prey-predator system where the prey exhibits herd behaviour. Positivity, boundedness, some extinction criteria, stability of equilibrium points are represented with some global results. Numerical computations are discussed to illustrate the analytical ﬁndings. The biological implications of analytical and numerical ﬁndings are represented. This work also has a direct bearing to the possibilities of developing conditions for ecological balance in nature and by elaborate study and analysis, it throws enough light on the scope of further work in this ﬁeld.